Laparoscopic Cholecystectomy in Situs Inversus Totalis with Left-Sided Gall Bladder - Kumar, Senthil (The Royal College of Surgeons of England, 2007)
Symptomatic gallstones in patients with situs inversus pose diagnostic and therapeutic challenges. The presentation and management of one such patient is discussed with an emphasis on operative technique.